Screening and Characteristics of Lactic Acid Bacteria from Cheese in Yili Area - Kai TANG; Yun WU; Xue WANG; Wenrui MA; Weilin CHEN; Zhenzhen ZHANG; Wenshu HUANG; Muying DU (Shipin gongye ke-ji)
In order to screen out lactic acid bacteria with excellent functional properties in traditional fermented food, in this study, the lactic acid bacterias in Yili cheese were effectively isolated and identified, as well as evaluation of their probiotic and functional characteristics. The lactic acid bacteria strains from Yili cheese were firstly isolated, followed by been identified by molecular biology techniques. Then, the lactic acid bacteria strains were screened based on several probiotic characteristics including acid tolerance, bile salt tolerance, auto-aggregation, hydrophobicity, and simulated gastrointestinal fluids tolerance. The functional characteristics of screened strains were further evaluated through determination of the free radical scavenging ability and α-glucosidase inhibition rate. The results showed that all isolated lactic acid bacteria strains (8 strains) from Yili cheese exhibited high acid and bile salt tolerance. In addition, the highest hydrophobicity (77.2%), the highest survival rate in gastric fluid (109.7%), and the highest survival rate in intestinal fluid (103.4%) could be found in Pediococcus acidilactici KT-7, KT-7 and Lactobacillus paracasei KT-2 strains, respectively. The antioxidant tests in fermentation supernatants showed that the KT-2 and Pediococcus pentosaceus KT-8 strains exhibited the best free radical scavenging ability for DPPH (79.8%) and hydroxyl radical (96.8%), respectively. The KT-2 and KT-7 strains provided high α-glucosidase activity inhibition rate more than 20%, still less than inhibition rate induced by KT-8 strain (34.9%). These findings provide three promising potential lactic acid bacteria strains (Lactobacillus paracasei KT-2, Pediococcus acidilactici KT-7, and Pediococcus pentosaceus KT-8) in functional fermented foods, mainly screened from Yili cheese with satisfied probiotic and functional characteristics.